Gallic acid and metformin co-administration reduce oxidative stress, apoptosis and inflammation via Fas/caspase-3 and NF-κB signaling pathways in thioacetamide-induced acute hepatic encephalopathy in rats - Ehsan Khedre Mohamed; Dawlat Mohamed Hafez (BMC, 2023)
Abstract Background Hepatic encephalopathy (HE) is a consequence of chronic or acute liver diseases. This study evaluates the combined effect of gallic acid (GA), and metformin (Met) on the liver and brain damage associated with HE. Methods Acute HE was induced by a single dose of thioacetamide (TAA) (300 mg/kg) as an I.P. injection. Treated groups received GA group (100 mg/kg/day, p.o), Met (200 mg/kg/day, p.o), or their combination for 25 consecutive days before TAA injection. Results The administration of TAA induced various biochemical and histopathological alterations. In contrast, treatment with GA either alone or combined with Met resulted in improved liver functions by the significant reduction in serum ALT, AST, and ALP activities, and ammonia levels. Inflammatory mediators; TNF-α, IL-6, and NFkβ levels were decreased by these treatments as well as apoptotic cascade via down-regulation of FAS and caspase-3 (CASP-3) expression in hepatic tissues. Furthermore, GA and Met either alone or combined protected the liver and brain tissues from damage by increased glutathione concentration while decreasing malondialdehyde. In addition, it was accompanied by the improvement of the brain neurotransmitter profile via the restoration of norepinephrine, dopamine, and serotonin levels. Based on our data, this is the first study to report a novel combined hepatoprotective and cognitive enhancing effect of GA and Met against TAA-induced acute liver and brain injury. Conclusion GA and Met combination resulted in a prominent improvement in HE complications, relative to monotherapy. Both agents potentiated the antioxidant, anti-inflammatory, and anti-apoptotic effects of each other.